Alkaline Activation of Basic Oxygen Furnace Slag Modified Gold Mine Tailings for Building Material - Tebogo Mashifana; Jessica Sebothoma; Thandiwe Sithole (Advances in Civil Engineering)
The mining industry generates large quantities of waste as tailings. The tailings have an adverse environmental impact. This study explored the utilization and stabilization of Barberton gold mine tailings (GMTs) and basic oxygen furnace slag (BOFS) to synthesize geopolymers for other applications. The geochemical, chemical, and geotechnical properties of GMT, BOFS, GMT geopolymer, and GMT: BOFS geopolymer were also studied. Sodium hydroxide (NaOH) and potassium hydroxide (KOH) were used as alkaline activators. The highest unconfined compressive strength (UCS) recorded for GMT geopolymers cured for 5 days at the elevated temperature of 90°C was 4.31 MPa and 6.59 MPa for NaOH and KOH, respectively. GMT: BOFS geopolymer attained the UCS of 20.0 MPa and 25.7 MPa, with NaOH and KOH, respectively, at the same curing conditions. Characterization of the binders showed that BOFS was a good source of calcium, which had a positive effect on the geopolymer gels by balancing the ionic charges. The developed GMT: BOFS geopolymers satisfied the minimum requirements for nonfacing building masonry as stipulated by the ASTM C34-17a, ASTM C129-14c 0076a, and the SANS 227: 2007 for burnt clay masonry units and can be used as a mine backfill paste and for lightweight civil applications. The geopolymers passed the toxicity characteristic leaching procedure (TCLP), and the results yielded low heavy metals concentration, indicating that the geopolymers will not leach to the environment.